Austenitizing Temperature and Quenching Media Effects on Hardness and Microstructure in Hardening of AISI 1040 Steel - Pangestu, Mulyo Aji; Rosidah, Afira Ainur (Fakultas Sains dan Teknologi, UNIRA Malang, 2024)
Hardening process is an important to make materials have harder properties related to wear resistance. This research determined the effects of austenitizing temperature and quenching media on the hardness and microstructure of AISI 1040. The austenitizing temperatures varies at 850°C, 900°C, and 950°C with PVA 10%, SAE 20W-50 oil, and salt water as quenching media. The method to measure hardness was the Brinell hardness test. The results showed changes in the microstructure from untreated steel with the structures of ferrite and pearlite to bainite and martensite. The highest hardness value of 416.22 kgf/mm2 was obtained in specimens with salt water media at an austenitizing temperature of 850°C.